Filaggrin compound heterozygous patients carry mutations in trans position. Issue 9 (16th August 2013) - Carlsen, Berit C.; Meldgaard, Michael; Johansen, Jeanne D.; Thyssen, Jacob P.; Menné, Torkil; Szecsi, Pal B.; Stender, Steen
Abstract More than 40 null mutations in the filaggrin (FLG) gene are described. It is therefore possible to find two different null mutations in one individual (compound heterozygosity). It has been generally perceived that homozygous and compound heterozygous individuals were genotypically comparable; however, this has not been scientifically investigated. Two different FLG null mutations in the same individual may be in trans position, meaning that each mutation locates to a different allele functionally equivalent to homozygosity, or may be in cis position, meaning that both mutations locate to the same allele functionally equivalent to heterozygosity. To experimentally investigate allelic in cis versus in trans configuration of the two most common filaggrin (FLG) mutations (R501X and 2282del4) in compound heterozygous individuals. Testing for in cis or in trans allele configuration was performed by means of allele‐specific PCR amplification and analysis of PCR products by agarose gel electrophoresis. All R501X/2282del4 compound heterozygous samples collected over a 4‐year period of routine FLG mutation testing were investigated. In total, 37 samples were tested. All thirty‐seven R501X/2282del4 compound heterozygous individuals were found to carry the two mutations in trans position. FLG null mutation compound heterozygous individuals can be considered functionally equivalent to FLG null mutation homozygosity for any of the two mutations.